Management of Non-Physical Special Allocation Funds for the Health Sector Health Operational Assistance at Community Health Centers during the Pandemic Period - Dina Indriyanti (International Journal of Integrative Sciences, 2023)
BOK (Health Operational Assistance) is a health budget that plays a role in pandemic times, but prone to deviations. This research assesses the governance of BOK funds in puskesmas using comparative analysis of applicable policies. The purpose of this study is to find out the effectiveness of the use of BOK funds through the suitability of the use of BOK funds with the Technical Instructions. The results of this study show that the financial management of BOK in puskesmas during the pandemic is considered quite effective, because it is in accordance with technical instructions BOK. Planning, administration, implementation of programs and activities, reporting and accountability are in accordance with regulations, albeit with various constraints. The evaluation of budget use is considered quite good with an achievement of more than 30% until the first semester of 2021